An analysis of the relative profitability of various thinning degrees in stands of Pinus patula in the eastern Transvaal - Joubert, A. F.(Andre Francois) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1964.